(3GdUMjaI GdcGedIs - (3GdbQTj GdgGTej, CHh GdMSf, Rjf GdYGHOjf, Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH, (B94(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; MOKfG GdSjO GdCLd fLe GdOjf HgGA GdTQa CHh GdMSf eMeO Hf GdMSf Hf CMeO Hf Ydj Hf eMeO Hf jMji GdYdhj GdMSjfj bGd CNHQfG GdTjN GdSYjO CHh YHO Gddg eMeO Hf CMeO Hf YeQ TgQjGQ GdNGRf dNRGfI ehdGfG CejQ GdeDefjf Ydj Hf CHj WGdHs
(3BNQgG (B:s
(3hGdG jJbOeg eJbOe hdG jJCNQ Yfg eJCNQ agh YUeg GddGjOjf hcga GdeDefjf hYQhI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 277s
(3eYLe GdeDdajf (B2 / 427s
(3GdPQjYI (B15 / 18s
(3GdJQGK GdYQHj (B48s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs